Performance Evaluation of Preventive Maintenance Considering Transportation Delays - Restrepo, Laura M. Ramirez; Aguezzoul, Aicha; Hennequin, Sophie (IFAC Proceedings Volumes, 2014)
This paper considers a production system of a single product, with constant transportation delays of items, between the machine and the buffer and between the buffer and the customer. The demand arrives with a constant rate. The system is modeled by a continuous-flow model. The machine is subject to time-dependent failures and the piloting policy is of hedging point type. We employed a preventive maintenance policy that is realized at each certain period. A performance evaluation of the system is made by simulation.